2021
DOI: 10.3390/antiox10060851
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Receptor Inhibitor Alleviates Metabolic and Inflammatory Changes in a Rat Model of Ischemic Stroke

Abstract: Hyperglycemia and inflammation, with their augmented interplay, are involved in cases of stroke with poor outcomes. Interrupting this vicious cycle thus has the potential to prevent stroke disease progression. Tumor necrosis factor-α (TNF-α) is an emerging molecule, which has inflammatory and metabolic roles. Studies have shown that TNF-α receptor inhibitor R-7050 possesses neuroprotective, antihyperglycemic, and anti-inflammatory effects. Using a rat model of permanent cerebral ischemia, pretreatment with R-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 56 publications
(101 reference statements)
2
20
0
Order By: Relevance
“…Therefore, the effects of AG490 on poststroke glucose metabolism were investigated. As shown in our previous reports [40][41][42][43], rats with cerebral ischemia developed hyperglycemia (Figure 3A), hyperinsulinemia (Figure 3B), and glucose intolerance (Figure 3C,D). AG490 displayed an alleviative effect on hyperglycemia (Figure 3A) and post-load glucose levels (Figure 3C,D), and augmented hyperinsulinemia (Figure 3B).…”
Section: Ag490 Improved Poststroke Hyperglycemiasupporting
confidence: 84%
See 3 more Smart Citations
“…Therefore, the effects of AG490 on poststroke glucose metabolism were investigated. As shown in our previous reports [40][41][42][43], rats with cerebral ischemia developed hyperglycemia (Figure 3A), hyperinsulinemia (Figure 3B), and glucose intolerance (Figure 3C,D). AG490 displayed an alleviative effect on hyperglycemia (Figure 3A) and post-load glucose levels (Figure 3C,D), and augmented hyperinsulinemia (Figure 3B).…”
Section: Ag490 Improved Poststroke Hyperglycemiasupporting
confidence: 84%
“…Therefore, the reduction of tissue IL-6 expression appears to be common upon beneficial intervention after cerebral ischemia. remained undetermined [40,43]. Tissues in both previous studies revealed an elevated IL-6 expression in the brain cortex, liver, and gastrocnemius of cerebral ischemia rats.…”
Section: Propranolol and R-7050 Alleviated Tissue Il-6 Expressionmentioning
confidence: 81%
See 2 more Smart Citations
“…We hypothesized that TFCJ might exert its neuroprotective effects by suppressing apoptosis and oxidative stress by activating the PI3K/Akt/mTOR signaling pathway. The important predictors of IS are the neurological deficit scores and cerebral infarction ( Zhang H. et al, 2020 ; Lin et al, 2021 ; Wang et al, 2021 ). In this study, rats were subjected to middle cerebral artery occlusion (MCAO) for 2 h and reperfusion for 24 h. In the early phase (first few minutes to a few hours) after intracerebral artery occlusion, the infarcted area containing ischemic tissue gradually spreads outwards.…”
Section: Discussionmentioning
confidence: 99%